Unimolecular decomposition rates of a methyl-substituted Criegee intermediate syn-CH3CHOO. Issue 14 (28th February 2020) - Li, Yu-Lin; Kuo, Mei-Tsan; Lin, Jim Jr-Min
Abstract : This work provides temperature dependent unimolecular rates of syn -CH3 CHOO at higher pressures. Abstract : Criegee intermediates play important roles in atmospheric chemistry. Methyl Criegee intermediate, CH3 CHOO, has two conformers, syn - and anti -conformers. Syn -CH3 CHOO would undergo fast unimolecular decomposition to form OH radical via 1, 4 H-atom transfer. In this work, unimolecular decomposition of syn -CH3 CHOO was probed in real time with UV absorption spectroscopy at 278–318 K and 100–700 torr. We used water vapor as the scavenger of anti -CH3 CHOO to distinguish the absorption signals of the two conformers. After removing the contributions from reactions with radical byproducts, reaction with water vapor and wall loss, we obtained the unimolecular reaction rate coefficient of syn -CH3 CHOO (at 300 torr), which increases from (67 ± 15) s −1 at 278 K, (146 ± 31) s −1 at 298 K, to (288 ± 81) s −1 at 318 K with an Arrhenius activation energy of ca. 6.4 kcal mol −1 and a weak pressure dependence for 100–700 torr. Compared to previous studies, this work provides temperature dependent unimolecular rates of syn -CH3 CHOO at higher pressures, which are more relevant to atmospheric conditions.